SIFAT FISIKA KAYU JABON (Anthocephalus cadamba Miq.) BERDASARKAN ARAH AKSIAL DARI DESA ALINDAU KABUPATEN DONGGALA SULAWESI TENGAH - Rahmayanti, Rahmayanti; Erniwati, Erniwati; Hapid, Abdul (Universitas Tadulako, 2016)
Scarcity of wood raw material can be solved by promoting fast growing tree species with a good quality of wood. Jabon (Anthocepalus cadamba Miq) is one of the species, which can be promoted to solve the scarcity. The objective of the research was to know physical properties of Jabon wood such as moisture content, specific gravity and change of wood dimension based on its axial position in the trunk (base, middle and top portions).Â The research has been realized from May to July 2014 at Laboratorium Agroteknology of Fakultas Pertanian, Universitas Tadulako Palu. The research used Jabon tree with six years old that showed 27 cm of diameter and 10 m of economical trunk originating from Alindau village of Central Sulawesi. The laboratory work of analyzing the wood samples has used British Standard 373: 157 by applying experimental design of Completely Randomized Design. The treatment was axial position that was divided into three positions: base, middle and top portions.Â The results show similarity on the moisture content of the positions, and as well as the change of wood dimension, meanwhile the specific gravity tend to increase trough base to top portions.Key Words:Â Jabon, Moisture content, specific gravityandchange of wood dimension